Combined MEK and PARP inhibition enhances radiation response in rectal cancer - Xiao, Qiyun; Riedesser, Julian; Mulholland, Theresa; Li, Zhenchong; Buchloh, Jonas; Albrecht, Philipp; Yang, Xinchen; Li, Moying; Venkatachalam, Nachiyappan; Skabkina, Olga; Klupsch, Anna; Eichhorn, Ella; et al. (Cell reports. Medicine, 2025)
Rectal cancer is frequently diagnosed at a locally advanced stage and treated by neoadjuvant chemoradiation. Current efforts to improve treatment outcome are focused on intensifying neoadjuvant chemotherapy, which is associated with higher levels of toxicity. To discover alternative strategies, we establish patient-derived rectal cancer organoids that reflect clinical radiosensitivity and use these organoids to screen 1,596 drug-radiation combinations. We find that inhibitors of rat sarcoma virus/mitogen-activated protein kinase (RAS-MAPK) signaling, especially mitogen-activated protein kinase kinase (MEK) inhibitors, strongly enhance radiation response. Mechanistically, MEK inhibitors suppress radiation-induced activation of RAS-MAPK signaling and selectively downregulate RAD51, a component of the homologous recombination DNA repair pathway. Through testing drug-drug-radiation combinations in organoids and cell lines, we identify that a combined poly ADP-ribose polymerase (PARP) and MEK inhibition can further enhance radiosensitivity of colorectal cancers, which we confirm in mouse xenograft models. Our data support clinical testing of MEK and PARP combination therapy with radiation in locally advanced rectal cancers as an alternative to chemoradiation.